Peanut (Arachis hypogaea) Shells Extract and Apis dorsata Honey Reduce Matrix Metalloproteinase-3 in Monosodium Iodoacetate-Induced Osteoarthritic Rats - Bella Stevanny; Tungki Pratama Umar; Junoretta Haviva Ernanto; Rachmat Hidayat (Faculty of Medicine, Diponegoro University, 2020)
Background: Osteoarthritis is the most common degenerative joint disease worldwide but its treatment can cause serious adverse events. Ethanol extract of peanut shells contains luteolin functioned as its main anti-inflammatory and chondroprotective agent. Apis dorsata honey also contains anti-inflammatory and antioxidant agent, especially from Tualang honey type. Both have the potential to reduce inflammation and prevent articular degradation in osteoarthritis.Objective: This study aims to determine the effect of peanut shells extract and Apis dorsata honey on matrix metalloproteinase-3 (MMP-3) level in monosodium iodoacetate-induced (MIA) osteoarthritic rats.Methods: In this in vivo study, female Wistar rats (n=27) were randomly divided to nine groups containing three rats each. Treatment was given to group 1, 2, and 3: Tualang honey (TH) 25% + peanut shells extract (PSE) with 1%, 5%, and 10% concentration; group 4, 5, and 6: TH 50% + PSE with 1%, 5%, and 10% concentration; group 7: diclofenac sodium (positive control); group 8: aquadest (negative control); and group 9: aquadest (normal) for 10 days. We induced knee osteoarthritis by intraarticular injection of MIA in day 4. Anti-inflammatory and chondroprotective activities were evaluated with MMP-3 ELISA.Results: The mixture of peanut shells extract and Apis dorsata honey significantly reduced MMP-3 level in group 1 (331.12 pg/ml), group 2 (291.73 pg/ml), group 3 (266.58 pg/ml), group 4 (274.15 pg/ml), group 5 (251.12 pg/ml), and group 6 (220.52 pg/ml) after 10 days of treatment. MMP-3 level was also evaluated in group 7 (169.61 pg/ml), group 8 (413.55 pg/ml), and group 9 (39 pg/ml). Compared to the negative control group, treatment and diclofenac groups showed significant effect in reducing MMP-3 level in patello-femoral articular cartilage.Conclusion: Peanut shells extract and Apis dorsata honey showed antiinflammatory and chondroprotective effect by reducing MMP-3 level in MIA-induced osteoarthritic rats.